2009
DOI: 10.1186/1748-717x-4-53
|View full text |Cite
|
Sign up to set email alerts
|

Audiological findings in patients treated with radio- and concomitant chemotherapy for head and neck tumors

Abstract: ObjectiveTo evaluate the functionality of the auditory system in patients who underwent radiotherapy and chemotherapy treatment with cisplatin to treat head and neck tumors.Study DesignCase series with planned data collection.SettingFrom May 2007 to May 2008 by the Department of Otorhinolaryngology and the Department of Oncology/Radiotherapy at Faculdade de Medicina de Marília.Subjects and MethodsAudiological evaluation (Pure Tone Audiometry (air and bone conduction), Speech Audiometry, Tympanometry, Acoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 13 publications
2
25
1
8
Order By: Relevance
“…Electrons are displaced in cancer tissues, by ionization, cause chemical and biological effects, such as DNA damage, that prevent the replication of neoplastic cells. It acts directly on the tumors and stops their multiplication by mitosis and/or determine cell death [3,6,14]. The literature also evince that chemoradiotherapy improves patient survival [15,16], but our participants had advanced cases and medical team reported the radiation therapy as an efficient procedure in cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrons are displaced in cancer tissues, by ionization, cause chemical and biological effects, such as DNA damage, that prevent the replication of neoplastic cells. It acts directly on the tumors and stops their multiplication by mitosis and/or determine cell death [3,6,14]. The literature also evince that chemoradiotherapy improves patient survival [15,16], but our participants had advanced cases and medical team reported the radiation therapy as an efficient procedure in cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer treatment has ototoxic effects that can damage hair cells, so it initially affects high frequencies, and it can also endanger low frequencies as a result of treatment exposure [3,5,14]. Literature reports an incidence of 26% and 85% of hearing loss, once 95% of hearing losses are sensorioneural [6].…”
Section: Controlmentioning
confidence: 99%
“…SNHL was observed in 43.33 % of patients and 16.67 % had mixed hearing loss 6 months post treatment. Dell'Aringa et al [14] observed that 17 patients with extra cranial head and neck malignancies included in the study presented with auditory damage with 70.5 % of them with having auditory alteration; 55.8 % with change higher than 20 dB in a unique frequency and 14.7 % with reduction of 10 dB in at least two consecutive frequencies. However, in the present study at the end of 16 weeks, 72.5 and 82.5 % of patients had SNHL at 4 and 8 kHz frequencies respectively which was clearly much above than the previous two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, hearing loss is sensorineural, bilateral and irreversible, tends to be permanent and it has tinnitus as a symptom [3,4]. It is a result of ototoxicity, which can damage cochlea`s basal turn and hits outer hair cells, before some days or weeks after cancer treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss affects either communication, social and emotional aspects; it may furhter reduce quality of life. Moreover, investigators have described hearing loss during cancer treatment, which can became worse (75% up to a 100%) especially in higher frequencies [3,5]. Audiological procedure, as conventional pure tone audiometry, is the basic of audiological battery for hearing loss diagnostic, once ototoxicity can develop a high frequency damage [6].…”
Section: Introductionmentioning
confidence: 99%